Irrigation Farming Adoption and Livelihood Outcomes among Smallholder Farmers in Uganda. A Cross-sectional Analysis - Vivien Akullo; Frank-Pio Kiyingi; Charles Edaku; Faustino Orach-Meza (International Journal of Global Health, 2026)
Introduction Agriculture is the backbone of Uganda’s rural economy, with smallholder farmers forming the majority of the farming population. Despite irrigation farming being recognized as a pathway to improved productivity and livelihood resilience, empirical studies on its adoption and outcomes in Uganda remain scanty. This limited evidence informed this cross-sectional analysis to evaluate how irrigation farming adoption influences smallholder farmers’ livelihoods in Uganda. Methods This study used a cross-sectional design to assess the link between irrigation adoption and livelihood outcomes among smallholder farmers in Uganda. From a target of 422 respondents, 387 participated (91.7% response rate). Districts, sub-counties, and farmers were purposively selected, with proportional representation to ensure balance. Data were analyzed using SPSS and STATA 18, applying descriptive statistics, Chi-square tests, regression, and logistic models. Assumptions of linearity and multicollinearity were checked, while Poisson regression and mixed models enhanced robustness. Results Adoption of modern irrigation technologies was generally low, with overall mean scores below 2.0 for drip, sprinkler, pump, hose pipe, and solar-powered systems, while small-scale manual methods showed moderate uptake (mean = 2.695, SD = 1.498). In contrast, livelihood outcomes were consistently high: agricultural productivity (mean = 3.802, SD = 0.688) reflected strong yields and profitability but moderate climate adaptation (mean = 2.907, SD = 1.241); income growth was notable (mean = 3.672, SD = 0.894); food security and social services were very high (means above 4.2), with clean water access scoring highest (mean = 4.455, SD = 0.529); and asset growth was positive (mean = 3.760, SD = 0.795). Overall livelihood outcomes averaged 3.963 (SD = 0.577). Correlation analysis showed a weak but significant positive relationship between irrigation adoption and livelihoods (r = 0.208, p = 0.000), while regression confirmed irrigation adoption significantly improved outcomes (β = 0.134, p = 0.000), explaining 4.1% of the variation.
Keywords: Irrigation Farming